PENGARUH JARAK TANAM TANAMAN PAGAR DAN DOSIS PUPUK KANDANG TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TOMAT(Lycopersicum esculentumMill) - Abd Syakur; Abd. Hadid; Lisa Irawati Sepena (Universitas Tadulako, 2016)
ABSTRACTThis research aimedwas to determine the effect of hedgerows planting distance and the rates of manure on growth and yield of tomato. This research was conducted in Bulupountu Jaya, Biromaru sub district, Sigi Biromaru district during December 2015 until March 2016. The study was compiled using a randomized block design (RBD) with two factors. The first factor wasplanting distances (P) with three levels i.e.10 cm x150 cm (p1), 20 cm x150 cm (p2) and 30 cm x150 cm (p3). The second factor was manure (K) consisting fourrates i.e. control (K0), 10 tons/ha (K1), 15 tons/ha (k2) and 20 tons/ha (K3). Each treatment was repeated three times, thus there were 36 experimental plots. The results indicated that the hedgerows plantingdistance and the manure rateshighly affected plant height leaf number, fruit weight and number of tomatoes fruits. The planting distance of 30 cm x150 cm with 20 tons chicken manure/ha resulted in best growth and highest yield of tomato plant. Keywords: Chicken manure rate, Hedgerows planting distance, Tomato Growth And Yield.